Biblia Sahidica : Ieremias, Lamentationes (Threni), Epistula Ieremiae et Baruch - Feder, Frank (Texte und Untersuchungen zur Geschichte der altchristlichen Literatur, 2002)
This volume presents a critical edition of the Coptic translation of the Corpus Ieremaie in the Coptic Sahidic dialect. It evaluates all the available texts (codices) and also considers secondary texts (lectionaries, quotations).